CANNABIS IN WEIGHT LOSS & METABOLIC DISEASES: A SYSTEMATIC REVIEW OF PRECLINICAL & CLINICAL STUDIES - Dr. Ankur Singh; Dr.Pushkar Manii; Dr Mohd Fazal Ahmed Makki (Journal of Population Therapeutics and Clinical Pharmacology, 2025)
The global obesity crisis continues to escalate, affecting over 650 million adults worldwide and driving the search for innovative therapeutic approaches. While cannabis has traditionally been associated with increased appetite— the well-known "munchies" effect—emerging evidence presents a fascinating paradox: regular cannabis users actually tend to have lower body weights and reduced rates of metabolic syndrome. This unexpected finding has sparked scientific interest in exploring whether specific cannabis compounds might offer therapeutic benefits for weight management and metabolic disorders. The endocannabinoid system, which regulates energy balance and metabolism, represents an intriguing target for these conditions. Objective: This systematic review aimed to comprehensively examine the scientific evidence surrounding cannabis- derived compounds and their potential role in treating obesity and metabolic diseases. We specifically focused on understanding how different cannabinoids—particularly cannabidiol (CBD) and Δ9-tetrahydrocannabivarin (THCV)— might influence weight loss, glucose control, and metabolic health through both laboratory studies and human clinical trials. Methods: We conducted an extensive search across major medical databases including PubMed, EMBASE, and Cochrane Central Register, covering research from the earliest available studies through October 2024. Our search strategy combined terms related to cannabis, individual cannabinoids, weight management, and metabolic conditions. We included both animal studies that help us understand biological mechanisms and human clinical trials that demonstrate real-world effects. Studies were carefully selected based on their scientific rigor and relevance to metabolic health outcomes. Results: Our analysis revealed compelling findings from 47 high-quality studies. The most striking discovery was the paradoxical relationship between cannabis use and body weight: while THC acutely increases appetite, chronic cannabis users consistently show lower BMI and reduced obesity rates in large population studies. THCV emerged as particularly promising, demonstrating CB1 receptor blocking properties that led to weight reduction and improved glucose control in animal models. In human trials, THCV at 5mg twice daily significantly lowered fasting blood glucose levels and enhanced pancreatic function in type 2 diabetes patients. More recent studies testing THCV/CBD combinations showed meaningful weight loss—up to 13.2% when combined with other treatments—along with improvements in blood pressure and cholesterol profiles. Importantly, these plant-derived compounds showed excellent safety profiles, contrasting sharply with the psychiatric side effects that led to withdrawal of the synthetic drug rimonabant. Conclusions: Cannabis-derived cannabinoids represent a promising new frontier in metabolic medicine, offering novel mechanisms for addressing obesity and diabetes. The evidence suggests these compounds work through multiple pathways: modulating appetite centers in the brain, improving insulin sensitivity in peripheral tissues, and reducing inflammation throughout the body. While current findings are encouraging, the field requires larger, longer-term clinical trials to fully establish efficacy and safety. The development of standardized, pharmaceutical-grade preparations and appropriate regulatory frameworks will be crucial for translating this research into effective treatments for patients struggling with metabolic disorders.